The The Influence of Digital Accounting Systems, Digital Financial Literacy, and Technology Capabilities on the Efficiency of Financial Statements of E-Commerce MSMEs - Pika Meri Yanti; Lisa Aulia Julica; Siti Fatimatul Khasanah; Purwanto Dimyati (Journal of Innovative and Creativity, 2025)
The development of e-commerce requires Micro, Small, and Medium Enterprises (MSMEs) to adapt to digital transformation, especially in the financial management and reporting process. However, some MSMEs still have difficulties in producing efficient financial reports due to limited recording systems, low digital financial literacy, and inadequate technological capabilities. This study aims to examine the influence of Digital Accounting System, Digital Financial Literacy, and Technology Capabilities on Financial Statement Efficiency in e-commerce-based MSMEs. This study uses a quantitative approach with an associative method. Data was collected through a questionnaire distributed to e-commerce MSME actors who have implemented digital financial recording, with purposive sampling techniques. Data analysis was carried out using multiple linear regression after going through validity, reliability, and classical assumptions tests. The results of the study show that the Digital Accounting System, Digital Financial Literacy, and Technology Capabilities have a positive and significant effect on the Efficiency of Financial Statements, both partially and simultaneously. These findings are expected to be an academic and practical contribution in supporting the improvement of the efficiency of digital-based MSME financial management.